Status of clipless laparoscopic cholecystectomy in a tertiary care hospital of Nepal: A descriptive cross-sectional study - Jha, Ashwini Kumar; Jha, Mina; Sah, Rajesh Kumar; Jha, Vinay Kumar; Yadav, Hem Shankar (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: In this modern age, the preferred course of treatment for gallstone disease symptoms is laparoscopic cholecystectomy. For securing both the cystic duct and artery with a single ligation (SLAD), is a quicker and safe procedure. The study was aimed to determine the status of clipless laparoscopic cholecystectomy in a tertiary care hospital of Nepal. Materials and Methods: A total of 205 patients with gallstone, who underwent laparoscopic cholecystectomy at tertiary center of Nepal of age group 16 - 70 years were included. During the procedure the cystic duct and artery was tied with single ligation. Data were subjected to Microsoft excel 16 for analysis. Results: Laparoscopic cholecystectomy was performed in 205 patients with gallstone. Average age of patients was 31.54 yrs. There was female predominance in the study. The cystic duct and artery were tied in single ligature using nonabsorbable Silk 2-0. The mean time taken for ligation was 120.78 ± 26.92seconds. Bile leakage and intra-op bleeding were found in two patients without any mortality. Conclusion: In laparoscopic cholecystectomy, a viable and secure alternate technique for securing the cystic artery and duct is single ligation with the use of non-absorbable thread. Even though it is a common procedure, it has an additional benefit over clips when dealing with thick, edematous cystic artery and duct complexes. It lowers the threat of surgical morbidity and does not increase the intra operative time.